A low temperature operated NO2 gas POF sensor based on conducting graft polymer - Maciak, Erwin; Sufa, Piotr; Stolarczyk, Agnieszka (Photonics Letters of Poland, 2014)
It has developed a simple POF sensor that is used to detection and measure concentration of nitrogen dioxide, at low temperatures (about 50°C). In this work, we present thermal profiling process of sensor head type POF, and application of sensing structure based on grafted polymer preparation by dip-coating technique. Were performed characterization prepared structures and tests with various concentration NO2 at low temperature and dry atmosphere. Full Text: PDF References E. Maciak, Z. Opilski, M. Urbanczyk, "Pd/V2O5 fiber optic hydrogen gas sensor", J. de Physique IV 129, 137 (2005). CrossRef T. Pustelny, M. Procek, E. Maciak, A. Stolarczyk, S. Drewniak, M. Urbanczyk, M. Setkiewicz, K. Gut, Z. Opilski, "Gas sensors based on nanostructures of semiconductors ZnO and TiO2", Bulletin of the Polish Academy of Sciences: Technical Sciences, 60(4), 853 (2012). CrossRef G. Mauthner, K. Landfester, A. Köck, H. Brückl, M. Kast, C. Stepper, E. J. W. List, "Inkjet printed surface cell light-emitting devices from a water-based polymer dispersion", Org. Electron. Physics, Mater. Appl. 9, 164 (2008). CrossRef A.Stolarczyk et al. Polish patent application nr P.407784 RR10.